EFFECTIVENESS STUDY OF THE CROSS-INTEREST PROGRAM IN MADRASAH ALIYAH NEGERI (MAN) - Hamlan Andi Baso Malla; Ambo Asrang (Universitas Tadulako, 2021)
Cross-interest learning or lessons learned by students of class IX Religion, become a challenge for students and educators in carrying out the learning process. This research is an initial study on the implementation of cross-interest learning which was developed based on the 2013 curriculum. In Madrasah Aliyah, cross-interests becomes interesting to study, especially in religion classes. Joining a religion class is input, process and output, and the obstacles to cross-interest implementation in class IX Religion. So that the implementation of cross-interest can be said to be effective. This paper aims to describe the results of a study on the effectiveness of cross-interest programs for grade IX students of religion at MAN I Poso. The study used a qualitative approach with data collection through observation, interviews and document studies, data were analyzed through data reduction, data presentation and data leveraging. The results showed that the cross-interest program at Madrasah Aliyah Negeri 1 Poso, especially in class XI Religion, was needed to accommodate the interests and talents of students to accommodate the potential of students.